Primary Evaluation of Anti-Inflammatory Effect of a Botanical Extract-Based Blend in a Haze Infected Cell Model. (29th May 2020) - Lu, Jihong; Jin, Lilan; Deng, Lu; Pan, Yixiao; Wang, Hai; Ren, Yiping; Stevenson, Doug; Liu, Chang; Bartlett, Mark
Abstract: Objectives: Exposure to air pollution has been associated with throat discomfort, cough, pulmonary disease, and even lung cancer. We developed a botanical extract-based blend with the goal of ameliorating some of the adverse effects of airborne pollutants. This blend consisted of broccoli seed (BS, Brasssica oleracea ) extract, Luo Han Guo (LH G, Siraitia grovenorii ) extract, and Honeysuckle Flower Bud (HFB, Lonicera japonica ) extract. BS extract is rich in Sulforaphane glucosinolate and is reported to promote healthy inflammatory balance as well as to regulate oxidative stress and DNA-damaging substances. LHG has been used as a traditional medicine for the treatment of pharyngitis, pharyngeal pain, as well as an antitussive remedy in China. HFB is a traditional herbal medicine widely used in East Asia as an anti-inflammatory and anti-oxidative agent. Methods: In order to evaluate the effectiveness of this putative airborne pollutant defense blend, human alveolar basal epithelial cells in adenocarcinoma (A549) were treated by exposing total culture medium (TCMed, to 0.02 mg/mL of haze particles (HP). Gene expression of inflammatory factors IL-1β, IL-8, TNF-α, INF-γ, and cell tight junction proteins were detected by qPCR at 0.5, 1, 2, and 6H when treated with 0.02 mg/mL HP TCMed alone (group H), 0.02 mg/mL HP TCMed + 5 mg/mL of LHG + HFB blend (LHG: HFB 1:10) +0.01 mg/mL of L-sulforaphane (group HT). Results: We found that gene expression of IL-1β, IL-8 and TNF-α were significantly decreased in HT at 1, 2, and 6 H treatment as compared to the F group. Gene expression of tight junction protein OCLN and ZO-1, which is a scaffolding protein, were significantly increased in HT as compared to the F group. Conclusions: This botanical extract blend regulates inflammatory factors and balances cell transmembrane stability in a primary cell haze infection model and therefore may be useful as a preventive formulation to help alleviate the adverse effects of airborne pollutants. Funding Sources: Nu Skin Enterprises.